Small-scale crop processing: opportunities and benefits - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Almost all crop and livestock products require some form of processing after harvest. This maybe in order to extend storage life or to facilitate cooking. Rural based processing offers opportunities in terms of employment, adds value to products,...